Liver-Specific, but Not Retina-Specific, Hepcidin Knockout Causes Retinal Iron Accumulation and Degeneration - Baumann, Bailey H; Shu, Wanting; Song, Ying; Sterling, Jacob; Kozmik, Zbynek; Lakhal-Littleton, Samira; Dunaief, Joshua L (American journal of pathology, 2019)
The liver secretes hepcidin (Hepc) into the bloodstream to reduce blood iron levels. Hepc accomplishes this by triggering degradation of the only known cellular iron exporter ferroportin in the gut, macrophages, and liver. We previously demonstrated that systemic Hepc knockout (HepcKO) mice, which have high serum iron, develop retinal iron overload and degeneration. However, it was unclear whether this is caused by high blood iron levels or, alternatively, retinal iron influx that would normally be regulated by retina-produced Hepc. To address this question, retinas of liver-specific and retina-specific HepcKO mice were studied. Liver-specific HepcKO mice had elevated blood and retinal pigment epithelium (RPE) iron levels and increased free (labile) iron levels in the retina, despite an intact blood-retinal barrier. This led to RPE hypertrophy associated with lipofuscin-laden lysosome accumulation. Photoreceptors also degenerated focally. In contrast, there was no change in retinal or RPE iron levels or degeneration in the retina-specific HepcKO mice. These data indicate that high blood iron levels can lead to retinal iron accumulation and degeneration. High blood iron levels can occur in patients with hereditary hemochromatosis or result from use of iron supplements or multiple blood transfusions. Our results suggest that high blood iron levels may cause or exacerbate retinal disease.
Keywords: Hepcidins; Iron Overload; Male; Mice, Knockout; železo; hematoretinální bariéra; Retina; mužské pohlaví; myši knockoutované; hepcidiny; Animals; ženské pohlaví; játra; Iron; přetížení železem; zvířata; Retinal Degeneration; Blood-Retinal Barrier; myši inbrední C57BL; myši; Mice, Inbred C57BL; degenerace retiny; retina; Liver; Mice; Female